A 3, 7‐Dihydroxyphenoxazine‐based Fluorescent Probe for Selective Detection of Intracellular Hydrogen Peroxide. Issue 6 (10th February 2016) - Han, Zhiqiang; Liang, Xiao; Ren, Xuejiao; Shang, Luqing; Yin, Zheng
Abstract: A novel N ‐borylbenzyloxycarbonyl‐3, 7‐dihydroxyphenoxazine fluorescent probe (NBCD) for detecting H2 O2 in living cells is described. The probe could achieve high selectivity for detecting H2 O2 over other biological reactive oxygen species (ROS). In addition, upon addition of H2 O2, NBCD exhibited color change from colorless to pink, which makes it a "naked‐eye" probe for H2 O2 detection. NBCD could not only be used to detect enzymatically generated H2 O2 but also to detect H2 O2 in living systems by using fluorescence spectroscopy, with a detection limit of 2 μm . Importantly, NBCD enabled the visualization of epidermal growth factor (EGF)‐stimulated H2 O2 generation inside the cells. Abstract : Ch‐ch‐ch‐ch‐changes : A new N ‐borylbenzyloxycarbonyl‐3, 7‐dihydroxyphenoxazine fluorescent probe (NBCD) for detecting H2 O2 in living cells is reported. NBCD was successfully used to detect intracellular H2 O2 with high selectivity and exhibited a color change from colorless to pink upon addition of H2 O2 .